IN SEARCH OF FOLKLORE IMPERATIVE: IVAN A. IL’YIN AND PHILOSOPHICAL THOUGHT OF THE RUSSIAN IMMIGRATION CIRCLE - Alex L. Nalepin (Studia Litterarum)
This article is part of the larger research project “Philosophical Thought of the Russian ‘Silver Age’ and Folklore.” Its aim is philosophical reflection of the Russian folk culture considering it as living tradition that largely determines the development of Russian civilization and the meanings of national mentality. Philological and philosophical branches of folklore studies are particularly important for the ongoing research of folklore and its role in national culture; philosophical folklore studies, for example, are concerned with ideological concepts and dominants of folk poetry. This article examines the choice of folklore vector in the work of Ivan Il’yin, a philosopher of Russian post-revolutionary Immigration diaspora in Europe. It for the first time introduces and motivates a concept of folklore imperative that dominated the late phase of Il’yin’s philosophical thought. Also, it introduces new materials that shed light on the study of this choice that was very important for Russian philosophy, literature, and culture as it was for Russian folklore studies.